ADOPTION OF SUSTAINABLE AGRICULTURAL PRACTICES AMONG SMALLHOLDER ROSELLE FARMERS IN JIGAWA STATE, NIGERIA - Isah, Sule; Musa., B., Muhammad; Mamman, B., Yarima; Usman, Kabir (FUDMA Journal of Sciences, 2026)
A 2025 study in Jigawa State, Nigeria, profiled 256 smallholder roselle farmers to understand why they do or do not adopt Sustainable Agricultural Practices (SAPs). Most farmers are male (95 %), married (78 %), 39 years old on average, and cultivate 3 ha inherited mainly through inheritance; 69 % have tertiary education, yet 73 % lack extension contact and 66 % belong to no cooperative. Awareness of SAPs is high: 88 % know crop rotation, 82 % optimum spacing, and 82 % organic manuring. However, actual adoption is driven by four significant factors: household size, farm size, roselle farming experience, and whether farming is the primary income source. The chief barriers are high input costs, limited credit, poor extension reach, and unstable roselle prices. To accelerate uptake, researchers recommend that the Jigawa State government introduce targeted incentives—subsidised improved seed, organic fertiliser, and low-interest loans—while recruiting and training more extension agents to deliver continuous technical backstopping and capacity building, ensuring roselle production becomes environmentally and economically sustainable for smallholders.
Keywords: Sustainable Agricultural Practices; Adoption; Roselle; Smallholder Farmers; Jigawa State; Nigeria